An Artificial Molecular Transporter. Issue 2 (30th December 2015) - Schäfer, Christian; Ragazzon, Giulio; Colasson, Benoit; La Rosa, Marcello; Silvi, Serena; Credi, Alberto
Abstract: The transport of substrates is one of the main tasks of biomolecular machines in living organisms. We report a synthetic small‐molecule system designed to catch, displace, and release molecular cargo in solution under external control. The system consists of a bistable rotaxane that behaves as an acid–base controlled molecular shuttle, whose ring component bears a tether ending with a nitrile group. The latter can be coordinated to a ruthenium complex that acts as the load, and dissociated upon irradiation with visible light. The cargo loading/unloading and ring transfer/return processes are reversible and can be controlled independently. The robust coordination bond ensures that the cargo remains attached to the device while the transport takes place. Abstract : Nanoscale logistics : We describe a bistable [2]rotaxane shuttle designed to catch, displace, and release molecular cargo in solution under external control. The cargo loading/unloading and ring displacement/return processes are reversible and can be controlled independently with optical and chemical stimuli, respectively. The robust coordination bond ensures that the cargo remains attached to the device during transport.